Kopisanangan (Hello/ Salam Sejahtera) / Chrisna Pindah - Pindah, Chrisna (Faculty of Art and Design, 2021)
The little girl on my painting is a girl that looking at me and my friend during a second day trip to paddy hill farm during a trip to Terian Village. She gave us a warm smile and shy face through her bamboo house. It is such a blessing to see a happy face of children. This image recalled my childhood memory back to 20 years ago. Back in September 2012; Me and my friend had visited of Penampang District in Sabah. I experience a lodging highway road, crossing a river without any bridge, a slippery and muddy road. After 2 and half hours with 4 wheel drive car, we arrived in a little heaven on earth. Because of the lovely people, cold weather and refreshing river flow sound down the village had great us infront the wonderful school. During this trip i experience a village activity such as fishing by the river, paddy hill planting, picking bambo shoot , visiting graveyard and the school. Terian Village of Penampang District in Sabah located in a small river valley and placed on the mighty Crocker Range. The value of this village is on its own minerals, The River. That is the reason the government of Sabah had been made a big proposal to make a new Dam in this village. Just to f boost the economy in town and Which means this project will drown at least 3-4 villagers nearby. As we know most of this area placed 2 secondary schools to provide education sources for the villagers (Children).